ANALISIS PROSEDUR PEMBERIAN KREDIT USAHA MIKRO PADA PT BANK BRI UNIT MAPPASAILE KABUPATEN PANGKEP - Hawang, Sitti; Hasyim, Sitti Hajerah; Nuraisyiah, Nuaisyiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
The aim of this research is to analyze the procedures for providing micro business credit to customers at Bank BRI Mappasaile Unit, Pangkep Regency. The data collection technique used is documentation. The data analysis design used in this research is descriptive analysis. As for the population and sample, the population in this study is all data relating to the Procedure for Providing Micro Business Credit to Customers at Bank BRI, Mappasaile Unit, Pangkep Regency. The sample in this study is the Procedure for Providing Credit at Bank BRI, Mappasaile Unit, Pangkep Regency for the 2022 financial year. From the results of the research, it shows that the procedures for granting micro business credit at Bank BRI, Mappasaile Unit, Pangkep Regency have been running well and effectively, in accordance with the procedures, conditions, criteria for whether they are eligible or not and the guidelines that have been set, but there are several things that must be addressed because they are still There are differences in recommending credit approval and granting credit approval.